On an Intersection of Principles of Philosophical Comprehension of History - Poviliūnas, Arūnas (Problemos, 1989)
In the paper the philosophical conceptions of history of I. Kant and J. G. Herder are contrasted and an attempt is made to find the role of the critical philosophy in the development of the philosophy of history. It is supposed, that in the critical philosophy of I. Kant for the first time the history of mankind manifested itself as the history of freedom. However, the view according to which the history presents by itself the formation of freedom, leads I. Kant to the counterposition of natural and intelligible worlds. Freedom as the prerequisite of morality and state as the prerequisite of freedom according I. Kant present by itself the main targets with the help of which the nature controls the history of mankind.